Single and hybrid antimalarials based on artemisinin, chloroquine and ß-lactams : synthesis, antiplasmodial activity, cytotoxicity and effect of selected artemisinin-chloroquine hybrids on the parasitic endocytosis pathway - Feng, Tzu-Shean (Department of Chemistry, 2014)
Includes abstract.